2018
DOI: 10.1002/joc.5394
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term rainfall regression surfaces for the Kruger National Park, South Africa: a spatio‐temporal review of patterns from 1981 to 2015

Abstract: ABSTRACT:As an important bottom-up driver of ecosystem processes, rainfall is intrinsically linked to the dynamics of vegetation and species distributions through its effects on soil moisture content and surface water availability. Rainfall effects are thus spatially and temporally specific to different environmental role-players. Knowledge of its spatio-temporal pattern is therefore essential to understanding natural ecosystem flux and potential climate change effects. Climate change poses a serious threat to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…The transition from dry to wet season typically occurs during late September and October in South Africa, and the year 2005 had slightly more rainfall than the climate average for Kruger National Park (MacFadyen et al . ). The African buffalo movement data we analysed indicates that the individual mostly occupied the northern and western extent of the region during the 2 weeks time period, but travelled c .…”
Section: Resultsmentioning
confidence: 97%
“…The transition from dry to wet season typically occurs during late September and October in South Africa, and the year 2005 had slightly more rainfall than the climate average for Kruger National Park (MacFadyen et al . ). The African buffalo movement data we analysed indicates that the individual mostly occupied the northern and western extent of the region during the 2 weeks time period, but travelled c .…”
Section: Resultsmentioning
confidence: 97%
“…This region is drier than the areas to the south and west where the other animals were sampled (MacFadyen et al, 2018). Rainfall within the KNP also varies from year-to-year (MacFadyen et al, 2018). This can affect the survival of the free-living stages of parasites, as well as host condition and population size, factors that can determine the susceptibility of individual hosts and the number of hosts available (Horak et al, 2003(Horak et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in mean flow volumes is apparently a human-driven process, since the decline is not consistent with the climatic conditions of the region (Figures S1 and S2). Rainfall and temperature in the Luvuvhu catchment have remained unchanged over the last 100 years [56]. Other studies in the LRC [20,22] have reported the rate of water abstraction for commercial forestry and agricultural purposes as an immediate concern for the sustainable future of stream flow regimes.…”
Section: Discussionmentioning
confidence: 99%